An Analysis of Inflectional Morphemes in a Short Story “The Child’s Story” by Charles Dickens - Ifadloh, Nur; Najerin, Muhammad Rizky; Nufus, Zahratun; Ulum, Miftakhul (SALEE: Study of Applied Linguistics and English Education, 2022)
This study aims to determine the inflectional morpheme contained in the short story entitled "The Child's Story" by Charles Dickens. The analysis shows that there are 108 inflectional morphemes found in the short story "The Child's Story". There are 35 plural nouns “-s”, “-es” with 32.5% percentage as the most dominant inflectional morphemes found in this story. Next, possessive nouns “-'s”, “-s'” and comparative adjectives “-er” both show 2 data (1.8%), superlative adjectives “-est” shows 3 data (2.7%), 3rd person singular/present tense “-s” shows 4 data (3.7%), verb past tense “-ed”/”-d” shows 29 data (26.9%), Present participle “-ing” shows 32 data (29.7%), past participle verb “-en” shows 1 data (0.9%). In addition, Inflectional does not change the grammatical category of words consisting of "-s, -'s, -er, -est, -s, -ed, -ing, and -en". The suffix “-s” means plural. The suffix “-'s”, “-s'” means possessive. The ending “-er” means comparative. The suffix “-est” means superlative. The ending “-ed” means past. The ending “-ing” means current (continuous). The ending “-en” means participle. Keywords: Morphology, Words, Inflectional, Morphemes, Suffixes.